A comparison of two conjunctival rotation autograft techniques in primary pterygium surgery - Karadag,Remzi (2017)
ABSTRACT Purpose: To compare the effects of 90° and 180° conjunctival rotational autograft (CRA) techniques used in primary pterygium surgery. Methods: Forty-five patients were included in this retrospective study. Visual acuity (VA), corneal topography, and auto-refractometer measurements, as well as detailed biomicroscopic examinations, were performed preoperatively and postoperatively. During surgery, the pterygium tissue was excised then rotated 90° in Group 1 and180° in Group 2, after which it was sutured to the bare sclera. Pterygium recurrence was defined as corneal invasion ≥1 mm. Results: Group 1 consisted of 21 patients with a mean age of 45.1 ± 11.8 years, while Group 2 comprised 24 patients with a mean age of 47.9 ± 13.8 years. The pterygia in Group 1 were graded as more advanced than those in Group 2. A similar number of recurrences were observed in Group 1 (14.3%) and in Group 2 (16.7%). There was no statistically significant difference in terms of the preoperative and postoperative VA and astigmatism values between the two groups. There was a statistically significant improvement in the postoperative VA and astigmatism values in Group 1 and in the postoperative astigmatism values in Group 2. Although postoperative redness was more common in Group 1, no statistically significant difference was found between the groups. Conclusion: BothCRA techniques can be successful in patients for whom it is desirable to avoid a conjunctival autograft and for patients without high cosmetic expectations.